The yeast pantothenate kinase Cab1 is a master regulator of sterol metabolism and of susceptibility to ergosterol biosynthesis inhibitors - Chiu, Joy E. (J Biol Chem, 2019)
In fungi, ergosterol is an essential component of the plasma membrane. Its biosynthesis from acetyl-CoA is the primary target of the most commonly used antifungal drugs. Here, we show that the pantothenate kinase Cab1p, which catalyzes the first step in the metabolism of pantothenic acid for CoA biosynthesis in budding yeast (Saccharomyces cerevisiae), significantly regulates the levels of sterol intermediates and the activities of ergosterol biosynthesis-targeting antifungals. Using genetic and pharmacological analyses, we show that altered pantothenate utilization dramatically alters the susceptibility of yeast cells to ergosterol biosynthesis inhibitors. Genome-wide transcription and MS-based analyses revealed that this regulation is mediated by changes both in the expression of ergosterol biosynthesis genes and in the levels of sterol intermediates. Consistent with these findings, drug interaction experiments indicated that inhibition of pantothenic acid utilization synergizes with the activity of the ergosterol molecule–targeting antifungal amphotericin B and antagonizes that of the ergosterol pathway–targeting antifungal drug terbinafine. Our finding that CoA metabolism controls ergosterol biosynthesis and susceptibility to antifungals could set the stage for the development of new strategies to manage fungal infections and to modulate the potency of current drugs against drug-sensitive and -resistant fungal pathogens.